A Palynological Atlas of the Amazon canga Vegetation - Luiza de Araújo Romeiro; Edilson Freitas da Silva; Luiza Santos Reis; Léa Maria Medeiros Carreira; Tarcísio Magevski Rodrigues; Delmo Fonseca da Silva; Tereza Cristina Giannini; Markus Gastauer; Pedro Walfir Martins e Souza-Filho; Lourival Tyski; José Tasso Felix Guimarães (Plants)
cangas are iron-rich outcrops where rupestrian fields develop in the Carajás Mountain Range (CMR). canga formations are ancient ecosystems characterized by high levels of endemic and threatened plant species that thrive on iron-rich substrates in the southeastern Amazon uplands. The recent taxonomic validation of these species enables more accurate distribution modeling across past, present, and future time scales. This work presents a comprehensive palynological database for the Amazon canga vegetation, resulting from extensive field and herbarium surveys, as well as the compilation and taxonomic validation of species in the Carajás Mountain Range (CMR). This atlas includes 204 plant species: 10 ferns and lycophytes, 62 monocots, and 132 eudicots and magnoliids (mainly herbs, lianas, and trees). Most flowering plants are pollinated by bees, with secondary pollination by other insects and wind. The taxa co-occur in two geoenvironments: (1) forested slopes and caves over plinthosols and ferralsols and (2) slopes with canga vegetation over plinthosols. Seventeen species are potential domesticates used by Indigenous peoples. This highlights canga vegetation as a unique and diverse ecosystem with various survival strategies, emphasizing the need for precise habitat definitions in paleoenvironmental and paleoclimate reconstructions. This atlas provides a valuable reference for palynological studies, enhancing the vegetation reconstruction, climate history analysis, pre-Columbian influences on vegetation patterns, and ecological monitoring.